Desenvolvimento de um equipamento para auxílio ao cálculo da difusividade térmica de alimentos - Souto, Huziel Ramos (2019)
This paper presents the development of equipment to assist the calculation of the thermal diffusivity of foods. From the study of the method used by DALIM researchers at UTFPR-CM, it was possible to automate part of the experiment and develop a dedicated equipment for it. Thus, the objective was to develop a temperature data acquisition and monitoring system used for the thermal diffusivity calculation, which makes the data available in a simple way, increasing the quality and practicality of the experiment, developing a thermostatic bath and integrating the temperature. the data acquisition system and the thermostatic bath developed. The execution of the equipment was divided into steps to optimize the process. The data acquisition and graphical interface equipment was the first to be developed and tested, using the Raspberry Pi 3B card, K-type thermocouples and MAX-6675 converters. Thereafter the thermostatic bath was developed. In its development the single-phase AC-AC converter with a 1000 W resistance was used. The thermal bath was integrated with the data acquisition system and tested, during the integration process there were no problems. The tests performed with the integrated equipment were successful and the results comply the requirements of the experiment. However, improvements include the implementation of a feedback temperature control and wireless communication system such as Bluetooth and Wi-Fi, which are native to the Raspberry Pi 3B card.